Response of Hybrid Rice to Transplanting Date and Nitrogen Fertilization under System of Rice Intensification in Rainfed Lowland Ecosystem - Singh, N. Anando; Pramanik, Kalipada; Sorokhaibam, Sakhen; Nabachandra, L.; Haribhushan, A. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted during kharif seasons of 2011 and 2012 at Imphal, Manipur to study the performance of hybrid rice PAC-801 to transplanting dates (6th July, 21st July and 5th August) and nitrogen levels (0, 60, 120 and 180 kg N ha-1) on productivity, profitability and nitrogen use efficiency under system of rice intensification in rainfed lowland condition. 21st July transplanted hybrid rice significantly increased panicles m-2 (17.9%), panicle length (4.6%), spikelets panicle-1 (13.7%), filled grains panicle-1 (17.7%), 1000-grain weight (2.17%), grain yield (12.4%) and straw yield (8.6%) over 5th August transplanting. Transplanting either on 6th July or 21st July produced significantly higher grain and straw NPK uptakes, agronomic efficiency and partial factor productivity of nitrogen than late transplanting on 5th August. Hybrid rice PAC 801 showed significant response to application of N up to 180 kg N ha-1 which improved the yield attributes (panicles m-2, panicle length, spikelets panicle-1, filled grains panicle-1), grain and straw yields and NPK uptakes of grain and straw. Maximum grain yield (7,169 kg ha-1) was with 180 kg N ha-1. This was 32.8, 13.3 and 2.2% higher over 0 (control), 60 and 120 kg N ha-1, respectively. Nitrogen fertilization beyond 60 kg ha-1 level significantly reduced agronomic efficiency, partial factor productivity and apparent recovery of applied nitrogen. Transplanting hybrid rice on 21st July along with nitrogen fertilization of 120 kg ha-1 resulted higher economical grain yield under rainfed lowland ecosystem as compared to rest of the treatments.